(untitled) (Research, Society and Development, 2021)
Since the arrival of the first samples of pesticides in Brazil the tradings of these chemicals has only increased. Therefore, the population is exposed to various classes of pesticides throughout their lives. Considering this the present study aims to review the use of pesticides in brazilian cultures to demonstrate the importance of the population’s knowledge and awareness about the consequences of the use of these products for public health. To do so data about the use of pesticides in agriculture and its consequences for the health of the population was collected through the use of descriptive-analytical-reflective methodology. Constant exposure to the various classes of pesticides represents a serious risk to public health, whether due to acute intoxications resulting from exposure to high concentrations in a short period, or to chronic intoxications resulting from contact with low concentrations for long periods. Even though agricultural workers and the population living around crops are more susceptible to the damage caused by these products, the consequences go beyond rural limits, reaching the entire population through food, water and air contaminated by these compounds. In conclusion it is necessary to increase researchs in this Field in order to understand the long-term consequences of the use of pesticides on health and the environment. It is also necessary to adjust surveillance actions in order to reduce the damage caused by the incorrect use of products as well to develop preventive and informative actions for all who use pesticides.